Padr\~ao de financiamento e exposiç\~ao cambial das empresas brasileiras a partir da crise de 2008 - Edison Benedito da Silva Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper aims to examine the evolution of currency risk exposure of Brazilian corporations, especially exporting companies, from the 2008 crisis, when several companies suffered substantial losses due to the decline of the real. We analyze their financial based on the usage of derivatives, as well as the impacts resulting from these contracts intermediation and reverberation of potential losses by the national banking system. We discuss also the effects of recent regulatory measures adopted by the Brazilian government in order to curb speculation in the currency market and establish a more effective monitoring of the risks associated with domestic derivatives.
Keywords: G01; G3; G32; G38; 330; financial crisis; corporate finance and governance; financial risk and risk management; government policy and regulation; Finanzkrise; Währungskrise; Unternehmensfinanzierung; Währungsmanagement; Brasilien